Quality-of-life among elderly with untreated fracture of neck of femur: A community based study from southern India - John D Prasad; Asha K Varghese; Dimple Jamkhandi; Arup Chakraborty; P S Rakesh; Vinod J Abraham (Journal of Family Medicine and Primary Care, 2013)
Background and Objectives: Owing to the high prevalence of osteoporosis and falls, elderly people are at risk of developing hip fractures. The objective of the current study is to assess the quality-of-life (QOL) of elderly (>60 years) with untreated hip fractures in a rural developmental block in Southern India. Methodology: Twenty-one elderly with an untreated fracture neck of femur were identified with the help of community level health workers. EuroQol (EQ-5D) was administered to assess the QOL before and after the event. QOL was also assessed among a comparison group, matched for age and sex among neighborhood people. Wilcoxon signed rank test and Mann-Whitney U test were used to compare EQ-5D mean scores with before the event scores and the comparison group scores respectively. Results: Of people with hip fracture, 57.1% (12/21), 76.2% (16/21), 81% (17/21), 52.6% (11/21) and 85.7% (18/21) reported severe problems with mobility, pain, usual activity, self-care and anxiety respectively. The EQ-5D mean score among the elderly with fracture neck of the femur was 0.08 (SD 0.27). It was low when compared with the same subjects before the occurrence of the event (Z –4.05, P < 0.001) and as compared with the comparison group (Z –5.77 P < 0.001). Conclusion: The QOL scores assessed using EQ-5D index scores was poor among people with untreated fracture neck of the femur as compared with the comparison group and also as compared to their status before the occurrence of the event. A vast majority of study participants reported severe problems with mobility, pain, usual activity and self-care and anxiety domains of EQ-5D questionnaire.